Dinamika Efisiensi Pasar dan Kompleksitas Struktural Pada Pasar Saham dan Cryptocurrency - Mahyudin, Roja Putera; Usmany, Alfrin Ernest Marthen (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2025)
This research aims to analyze the dynamics of market efficiency and structural complexity in traditional capital markets and digital asset markets through an econophysics approach. Utilizing the Multifractal Detrended Fluctuation Analysis (MFDFA) integrated with Empirical Mode Decomposition (EMD), this study examines daily data from the S&P 500, NASDAQ, Bitcoin, and Ethereum indices spanning from 2010 to 2024. The analytical results indicate that all tested assets are in a state of structural inefficiency, characterized by drastic variations in the generalized Hurst exponent (h(q))across various fluctuation orders. Although stock indices exhibit an average Hurst value near 0.5, the extreme singularity spectrum width (∆α > 0.8) proves the existence of non-linear scaling laws that reject the Efficient Market Hypothesis (EMH). Digital assets, particularly Bitcoin, demonstrate the highest degree of multifractality (∆α = 0.9352) and strong persistence (H = 0.5581), indicating the dominance of long-term memory and high sensitivity to speculation. These findings confirm the existence of "irrational exuberance" as proposed by Robert Shiller, where pricing mechanisms are driven more by herding behavior and information shocks than by fundamental values. The study concludes that modern financial markets, especially the cryptocurrency sector, possess a complex fractal structure that necessitates a non-linear risk management approach.